Influência de fatores metabólicos e genéticos no emagrecimento induzido por um programa de treinamento aeróbio e pessoas sedentárias e obesas - Fonseca, Herik Vieira de Carvalho (2024)
Introduction: Physical exercise is often recommended as a strategy for the treatment of overweight and obesity, yet literature has demonstrated that its efficacy is somewhat limited. This may be attributable to genetic, physiological, and environmental factors which may exert a negative influence. Objective: To analyze the impact of the rs9939609 polymorphism of the FTO gene, systemic inflammation, oxidative stress, and lipid profile on the extent of weight loss induced by aerobic training in individuals with overweight and/or obesity. Methodology: This study involved 129 volunteers of both sexes, previously inactive, with overweight and obesity, who participated in two studies. In Study 1, aimed at examining the influence of the rs9939609 polymorphism of the FTO gene on weight loss induced by aerobic training, 87 individuals of both sexes, previously inactive, with overweight or obesity (33.8 ± 9.09 years of age and BMI 31.3 ± 3.27 kg/m²), were divided into intervention (n=70) and control (n=17) groups. The intervention group partook in a 12-week aerobic training regimen, whereas the control group was instructed to maintain the same sedentary lifestyle throughout the 12 weeks. The intervention group was further subdivided by genotype into TT (n=21) and TA (n=49). All participants were assessed for aerobic capacity (ergospirometry), body composition (DXA), waist and hip circumference, nutritional evaluation, and lipid profile before, at the sixth week, and 48 hours following the experimental protocol. In Study 2, which aimed to analyze the association of systemic inflammation, oxidative stress, and lipid profile with the magnitude of weight loss induced by aerobic training in individuals with overweight and/or obesity, 58 volunteers were divided into intervention (n=38) and control (n=20) groups. The intervention group engaged in a 12-week aerobic training program, while the control group was advised to maintain the same sedentary lifestyle for 12 weeks. Assessments were made regarding body composition (bioimpedance), waist and hip circumference, lipid profile, oxidative stress, and systemic inflammation at the beginning and end of the training program.. The training program consisted of aerobic exercises, including running and walking, at an intensity of 65 to 75% of maximum heart rate, with a duration of 40 to 60 minutes per session and frequency of 3 to 5 sessions per week. Statistical Analysis: The data were treated using a two-way ANOVA for repeated measures, with Tukey's post hoc test and Pearson's correlation test. Results: In Study 1, the intervention group showed a significant reduction in fat mass (1.1 ± 1.9 kg; p<0.00), body fat percentage (1.1 ± 1.6%; p<0.00), waist circumference (1.9 ± 3.1 cm; p<0.00), and hip circumference (2.4 ± 4 cm; p<0.00) between pre- and post-intervention, with no significant time x group interaction. The allele frequency observed was 30% for the TT allele and 70% for the TA allele. The TA group significantly reduced fat mass (1.1 ± 2 kg; p<0.00), body fat percentage (1.1 ± 1%; p<0.00), waist circumference (1.5 ± 3.3 cm; p<0.00), and hip circumference (3.0 ± 4.4 cm; p<0.00). For the TT genotype, the reduction was significant only for body fat percentage (1.1 ± 1.6) and waist circumference (2.8 ± 2.3). The TA group showed a reduction in cholesterol (13.7 ± 19; p<0.04) and triglycerides (22 ± 60.3; p<0.03), whereas the TT group did not show significant reductions for these variables. In Study 2, the intervention group reduced body mass (-1.9 ± 11.3 kg; p<0.00), BMI (-0.8 ± 1.36 kg/m²; p<0.00), fat mass (-2 ± 3.1 kg; p<0.00), body fat percentage (-1.3 ± 2.4; p<0.00), and waist circumference (-2.2 ± 3.6; p<0.00). In the association of metabolic variables with body composition variables, there was a positive association (r=0.36) between post-training HDL and BMI, and with lean mass (r=0.39). Among cytokines, there was a negative association between IL-17 and waist circumference (r=-0.53), and with the delta (r=-0.42); INT-γ showed a negative correlation (r=-0.31), and post-training IL-6 values correlated positively (r=0.32) with body fat percentage, IL-10 correlated positively (r=0.34) with BMI, and also showed a weak positive correlation (r=0.43) with hip circumference. Conclusion: The FTO gene polymorphism, along with certain metabolic conditions (lipid profile of HDL lipoproteins, and cytokines IL-17, INT-γ, IL-6, and IL-10), has a slight influence on body composition response variables to physical training.